Controlled molecular self-assembly of complex three-dimensional structures in soft materials - Huang, Changjin (2019)
Many applications in tissue engineering, flexible electronics, and soft robotics call for approaches that are capable of producing complex 3D architectures in soft materials. Here we present a method using molecular self-assembly to generate hydrogel-based 3D architectures that resembles the appealing features of the bottom-up process in morphogenesis of living tissues. Our strategy effectively utilizes the three essential components dictating living tissue morphogenesis to produce complex 3D architectures: modulation of local chemistry, material transport, and mechanics, which can be engineered by controlling the local distribution of polymerization inhibitor (i.e., oxygen), diffusion of monomers/cross-linkers through the porous structures of cross-linked polymer network, and mechanical constraints, respectively. We show that oxygen plays a role in hydrogel polymerization which is mechanistically similar to the role of growth factors in tissue growth, and the continued growth of hydrogel enabled by diffusion of monomers/cross-linkers into the porous hydrogel similar to the mechanisms of tissue growth enabled by material transport. The capability and versatility of our strategy are demonstrated through biomimetics of tissue morphogenesis for both plants and animals, and its application to generate other complex 3D architectures. Our technique opens avenues to studying many growth phenomena found in nature and generating complex 3D structures to benefit diverse applications.